The low PLC-δ1 expression in cystic fibrosis bronchial epithelial cells induces upregulation of TRPV6 channel activity. Issue 1 (January 2015) - Vachel, Laura; Norez, Caroline; Jayle, Christophe; Becq, Frédéric; Vandebrouck, Clarisse
Graphical abstract